2022
DOI: 10.1101/2022.01.24.477423
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

P38 kinases mediate NLRP1 inflammasome activation after ribotoxic stress response and virus infection

Abstract: Inflammasomes integrate cytosolic evidence of infection or damage to mount inflammatory responses. The inflammasome sensor NLRP1 is expressed in human keratinocytes and coordinates inflammation in the skin. We found that diverse stress signals converge on the activation of p38 kinases to initiate human NLRP1 inflammasome assembly: UV irradiation and microbial molecules that initiate the ribotoxic stress response critically relied on the MAP3 kinase ZAKα to activate p38 and ultimately human NLRP1. Infection wit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 63 publications
1
7
0
Order By: Relevance
“…We have expanded the repertoire of known human NLRP1 agonists to include multiple microbial ribotoxins such as ANS and DON. The same results have been independently reported by a concurrent study ( 40 ). Our work raises several questions to be addressed by future studies.…”
supporting
confidence: 88%
“…We have expanded the repertoire of known human NLRP1 agonists to include multiple microbial ribotoxins such as ANS and DON. The same results have been independently reported by a concurrent study ( 40 ). Our work raises several questions to be addressed by future studies.…”
supporting
confidence: 88%
“…Oxidized cysteine can then be targeted for arginilation and be degraded via the Arg/N-end rule pathway, that it is therefore considered as a NO/O 2 sensor pathway involved in the elimination of misfolded proteins [ 81 ]. In addition, other PTMs events have been reported to modulate NLRP1 since MAPK kinases ZAKα, p38 and c-Jun N-terminal kinase (JNK) could induce NLRP1 activation via phosphorylation, particularly in response to UV radiations [ [82] , [83] , [84] ]. This evidence may suggest a similar mechanism for O 3 that has been found to modulate these kinases especially in the airway inflammatory response [ [85] , [86] , [87] ].…”
Section: Discussionmentioning
confidence: 99%
“…UVB-induced NLRP1 activation requires the activity of the stress-induced protein kinases p38 and JNK [ 113 ]. Recently, it was shown that this is induced by the kinase ZAKα (leucine-zipper and sterile-alpha motif kinase) [ 114 , 115 ] upon activation of the ribotoxic stress response (RSR) pathway [ 116 ] ( Figure 2 ). The RSR is induced by the collision of ribosomes upon UVB radiation and sensed by ZAKα binding directly to the ribosomes.…”
Section: The Nlrp1 Inflammasomementioning
confidence: 99%
“…Then, ZAKα is activated, inducing phosphorylation of p38 and JNK. Finally, activated ZAKα and p38 directly activate NLRP1 by phosphorylation [ 114 , 115 ]. In non-stressed cells, NLRP1 is inhibited upon binding to DPP8 (dipeptidyl peptidase 8) and 9, partially via interaction of the aminoterminus of NLRP1-CT with the active site of the peptidases [ 117 , 118 ].…”
Section: The Nlrp1 Inflammasomementioning
confidence: 99%
See 1 more Smart Citation